Methodology of Examination and Analysis of the Speech of Children with Not Completely Developed Speech Based on Creative Approaches - Sidikova, Yulduz Sobirovna; Kadirov, MuhammadKadir Zakirovich (European Journal of Life Safety and Stability (2660-9630), 2022)
In this article, on the basis of creative approaches, the method of checking and analyzing the speech of children whose speech is not fully developed , the correct understanding of the speech defect and its effective impact on it, a more correct and short way to eliminate it. In order to choose the most important issues such as knowing how to determine the nature of speech disorders, their depth and level, learning how these defects affect the speech system, important aspects were purposefully analyzed.